Empat Koreografer Tari Kontemporer Indonesia Periode 1990-2008 - Supriyanto, Eko; Haryono, Timbul; -, R.M. Sudarsono; Murgiyanto, Sal (PANGGUNG, 2014)
ABSTRACTÃÂ This research will elaborate four Indonesian contemporary choreographers, which lead to open the significant of embodiment process on Indonesian dancers. With a focus on four choreographers, Mar- tinus Miroto, Mugiyono Kasido, Hartati, and Jecko Siompo. A case study of body of those four choreo- graphers has reached its Ã¢â¬ÅinstitutionalÃ¢â¬Â level, so choosing those four characters, as a representation of Indonesian dancer is the right thing to do. With the complexity discipline and body work training, the four dancers and choreographer strengthening on how procession to achieve and advancing body work is located in some important process: exercise, training, and performance. This is diÃ¯Â¬â¬erent from the pro- cess of body works quality and the achievement of most dancers and choreographer outside of Indonesia. Usually the dancers outside of Indonesia only stress on two things: Training and performance. The four dancers in the work have had a typical body works each of them, but it is undeniable that there is a role in the respective Sardono as the maestro. SardonoÃ¢â¬â¢s strong influence thus again took place in forming a model to the body or body-dance attitude of dancers who then the outcome was, in fact, diÃ¯Â¬â¬erent from SardonoÃ¢â¬â¢s works.ÃÂ Keywords: contemporary, embodied, training, rehearsal, performanceÃÂ ÃÂ ABSTRAKÃÂ Penelitian ini membahas empat koreografer, dalam membuka wacana proses ketubuhan penari di Indonesia. Empat koreografer tersebut, Martinus Miroto, Mugiyono Kasido, Hartati, dan Jecko Siompo, memperlihatkan betapa kompleksitas proses ketubuhan mereka berbeda dengan penari dan koreografer pada umumnya, terutama dari luar Indonesia. Mereka mem- berikan pengalaman yang detail tentang pendisiplinan tubuh mereka untuk mencapai sebuah capaian dan keunggulan. Dengan kompleksitas disiplin dan training ketubuhan, keempat penari dan koreografer ini menggukuhkan betapa proses pencapaian dan kemuktahiran tubuh terletak pada beberapa proses penting: Training, Latihan, dan Pementasan. Jika ditilik secara ke- seluruhan, keempat penari ini mempunyai pengalaman belajar, atau setidaknya pernah men- galami proses menari bersama Sardono W. Kusumo. Ketubuhan yang yang dieksplorasi adalah ciri khas dari Sardono yang dikenal dengan laku dalam bahasa Jawa. Walaupun belajar dari Sar- dono, keempat koreografer tersebut mengembangkan tarian yang berbeda dengan Sardono.ÃÂ Kata kunci: kontemporer, ketubuhan, training, latihan, pementasan